ANALISIS FENOMENA CHILDFREE MENURUT PERSPEKTIF IMAM AL-GHAZALI - Persada, Bahtera; Dinnar, Malik; Ardiansyah, Rio; Fasyaya, Qiyan (Program Studi Perbandingan Mazhab, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2023)
An ideal family consist of father, mother and child. This concept was deeply embedded society. Based on the stereotype, many married couples followed or made pregnancy programme soon after getting married, Howefer, times passed and development is inevitable. Nowadays, a family with child is not the only concept for marriage. Some couples started to have a childfree. It is a family without biological child. This phenomenon comes as polemic especially for moslems. As we know, in Islam a couple married is suggested to have children as descendants. Furthermore, having many children is considered as Sunnah to follow Rasulullah SAW. This research will be conducted using descriptive qualitative method viewed thought subjective approach by imam Al-Ghazali. Based on perspective of imam Al-Ghazali, childfree may be done in certain condition, for example to reduce mafsadat in marriage life in ‘azl way.